Tingkat Pengetahuan Gizi, Konsumsi Buah Dan Sayuran, Dengan Status Gizi Penderita Hipertensi - Irza Nanda Ranti; I Made Djendra; Rudolf B. Purba; Riviany Olivia Sumoked (POLTEKKES KEMENKES MANADO, 2018)
The World Health Organization (WHO) notes that the world's population suffering from hypertension is among those in low- and middle-income developing countries. Indonesia is in a row of 10 countries with the highest prevalence of hypertension in the world. This study aims to determine the level of nutritional knowledge, consumption of fruits and vegetables, and nutritional status of hypertensive patients in the work area of ​​Ranomuut Puskesmas Manado. The type of this research is analytical descriptive with crossectional design. With an average rating of 125 people / month. The samples taken were 42 patients with hypertension. The instrument used in this study is a nutritional knowledge questionnaire, Form Spring Food Frequency Questioner (FFQ). Digital tension meter, scales and Mikrotoa. Data analysis using Fisher Exact Test to know relation of independent and bound variable. The results of this study indicate that there are 14.2% of people with good nutritional knowledge and 42.9% moderate knowledge level and 42.9% less nutritional knowledge level. And there are 52.4% of people who consume good fruit and most there is 61.9% of people less vegetable consumption. And most hypertensive patients have obesity nutritional status. There was no significant relationship between nutritional knowledge level and nutritional status (p = 0.115). There was a significant relationship between vegetable consumption and nutritional status (p = 0.039). There was a significant relationship between fruit consumption and nutritional status (p = 0.049).